BASI74, a Virulence-Related sRNA in Brucella abortus - Dong, Hao; Peng, Xiaowei; Liu, Yufu; Wu, Tonglei; Wang, Xiaolei; De, Yanyan; Han, Tao; Yuan, Lin; Ding, Jiabo; Wang, Chuanbin; Wu, Qingmin (Frontiers in Microbiology, 2018)
Brucella spp. are intracellular pathogens that infect a wide variety of mammals including humans, posing threats to the livestock industry and human health in developing countries. A number of genes associated with the intracellular trafficking and multiplication have so far been identified in Brucella spp. However, the sophisticated post-transcriptional regulation and coordination of gene expression that enable Brucella spp. to adapt to changes in environment and to evade host cell defenses are not fully understood. Bacteria small RNAs (sRNAs) play a significant role in post-transcriptional regulation, which has already been confirmed in a number of bacteria but the role of sRNAs in Brucella remains elusive. In this study, we identified several different sRNAs in Brucella spp., and found that over-expression of a sRNA, tentatively termed BASI74, led to alternation in virulence of Brucella in macrophage infection model. The expression level of BASI74 increased while Brucella abortus 2308 was grown in acidic media. In addition, BASI74 affected the growth ratio of the Brucella cells in minimal media and iron limiting medium. Using a two-plasmid reporter system, we identified four genes as the target of BASI74. One target gene, BABI1154, was predicted to encode a cytosine-N4-specific DNA methyltransferase, which protects cellular DNA from the restriction endonuclease in Brucella. These results show that BASI74 plays an important role in Brucella survival in macrophage infection model, speculatively by its connection with stress response or impact on restriction-modification system. Our study promotes the understanding of Brucella sRNAs, as well as the mechanism by which sRNAs use to influence Brucella physiology and pathogenesis.